Measuring Intratumoral Heterogeneity of Immune Repertoires - Yuzhakova, Diana Vladimirovna; Volchkova, Lilia N.; Pogorelyy, Mikhail Valerievich; Serebrovskaya, Ekaterina O.; Shagina, Irina A.; Bryushkova, Ekaterina A.; Nakonechnaya, Tatiana O.; Izosimova, Anna V.; Zavyalova, Daria S.; Karabut, Maria M.; Izraelson, Mark; Samoylenko, Igor V.; et al. (Frontiers in Oncology, 2020)
There is considerable clinical and fundamental value in measuring the clonal heterogeneity of T and B cell expansions in tumors and tumor-associated lymphoid structures—along with the associated heterogeneity of the tumor neoantigen landscape—but such analyses remain challenging to perform. Here, we propose a straightforward approach to analyze the heterogeneity of immune repertoires between different tissue sections in a quantitative and controlled way, based on a beta-binomial noise model trained on control replicates obtained at the level of single-cell suspensions. This approach allows to identify local clonal expansions with high accuracy. We reveal in situ proliferation of clonal T cells in a mouse model of melanoma, and analyze heterogeneity of immunoglobulin repertoires between sections of a metastatically-infiltrated lymph node in human melanoma and primary human colon tumor. On the latter example, we demonstrate the importance of training the noise model on datasets with depth and content that is comparable to the samples being studied. Altogether, we describe here the crucial basic instrumentarium needed to facilitate proper experimental setup planning in the rapidly evolving field of intratumoral immune repertoires, from the wet lab to bioinformatics analysis.